Moderation of Environmental Performance on the Influence of Environmental Management Accounting and Green Innovation on Firm Value - Dewi, Ni Wayan Candrawati; Purnamawati, I Gusti Ayu; Musmini, Lucy Sri (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study was conducted to examine the relationship between Environmental Management Accounting (EMA) and green innovation on firm value with the moderation of environmental performance. The research was carried out on manufacturing companies, with a population of all manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2022–2024, totaling 171 companies. The sample was selected using purposive sampling, resulting in 79 companies that met the criteria, and with a three-year observation period, 237 financial reports were obtained. Data collection was conducted using documentation methods and analyzed with Moderated Regression Analysis (MRA) using STATA software. The results show that both EMA and green innovation partially have a positive and significant effect on firm value, while environmental performance does not strengthen the relationship between EMA and firm value nor between green innovation and firm value.